Appraisal of the Constituent Plant Materials in a Ghanaian Antifungal Herbal Product; An in vitro Interactive Combination Analysis and a Pilot Clinical Study to Determine Efficacy. - Kwesi Prah Thomford; Merlin Lincoln Kwao Mensah; Rita Akosua Dickson; Ama Kyeraa Thomford; Alfred Ampomah Appiah; Stephen Yao Gbedema (International Journal of Phytomedicine, 2018)
Evidence based use of herbal medicines has a positive implication for both users and society. In this study, component plant materials of a traditional Ghanaian polyherbal skin product comprising Eugenia caryophyllata, Zanthoxylum zanthoxyloides Tridax procumbens, Psidium guajava and Alchornea cordifolia and used in the management of superficial skin infections was evaluated to establish their contribution to the overall therapeutic activity of the product. Each of the five (5) plants was subjected to an in vitro antimicrobial assay using the microtitre broth technique followed by an interactive combination assay for plants demonstrating noteworthy antimicrobial activity (MIC ≤ 1.0 mg/ml). Test strains included Staphyloccocus aureus, Candida albicans, Trichophyton rubrum, Epidermophyton floccusum and Microsporum canis. Eugenia caryophyllata, Zanthoxylum zanthoxyloides and Alchornea cordifolia showed better activity than Psidium guajava, Tridax procumbens and the Total Crude Extract (combination of the 5 extracts). The binary combination of Eugenia caryophyllata and Alchornea cordifolia indicated synergistic and additive activity against all the test strains. An improved biological activity was also observed when a mixture of the two (2) plants at a ratio of Eugenia caryophyllata 60 % (w/w) and Alchornea cordifolia 40 % (w/w) was assayed. A follow up pilot clinical study established that this new recipe was clinically effective but of lower therapeutic effect compared to the original product. In conclusion, the original formulation of the product may be preferred because of the shorter duration of treatment which reduces the risk of harms and cost of treatment.